2021
DOI: 10.1007/s10900-021-01039-3
|View full text |Cite
|
Sign up to set email alerts
|

Active Surveillance of Adverse Events in Healthcare Workers Recipients After Vaccination with COVID-19 BNT162b2 Vaccine (Pfizer-BioNTech, Comirnaty): A Cross-Sectional Study

Abstract: In this cross-sectional study, adverse events after the first and second dose of BNT162b2 mRNA (Pfizer-BioNTech, Comirnaty) vaccine against coronavirus disease 2019 were investigated among employees of clinics in central Italy. A 42-items questionnaire was administrated to vaccine recipients. Adverse events were classified based on severity and occurrence as reported in the literature. A descriptive/univariate analysis using Chi-square or Fisher’s Exact tests was performed. Odds ratio (OR) and 95% confidence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
49
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 43 publications
10
49
0
Order By: Relevance
“…Coronavirus disease 2019 (COVID-19) is a life-threatening condition [ 1 , 2 ] caused by severe acute respiratory coronavirus 2 syndrome (SARS-CoV-2) [ 1 ], being worldwide lethal in ~2% of cases [ 2 ]. To reduce its morbidity and mortality, the most efficacious prevention strategy is vaccination [ 2 ]. Healthcare workers are one of the principal targets of vaccination because of their occupational exposure [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Coronavirus disease 2019 (COVID-19) is a life-threatening condition [ 1 , 2 ] caused by severe acute respiratory coronavirus 2 syndrome (SARS-CoV-2) [ 1 ], being worldwide lethal in ~2% of cases [ 2 ]. To reduce its morbidity and mortality, the most efficacious prevention strategy is vaccination [ 2 ]. Healthcare workers are one of the principal targets of vaccination because of their occupational exposure [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…To reduce its morbidity and mortality, the most efficacious prevention strategy is vaccination [ 2 ]. Healthcare workers are one of the principal targets of vaccination because of their occupational exposure [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…both considering the general population or even HCWs [2,3]. In this regard, it is worth mentioning a cross-sectional study recently published by Ripabelli, also enrolling HCWs, found that age under 55 years was a predictor for AEFIs [7], supporting findings from Ponticelli and colleagues. Further research should explore possible factors other than age and sex, which might influence AEFIs occurrence, including health status and comorbidities.…”
mentioning
confidence: 55%
“…In light of the surge of virulent variants, and the reduction of effectiveness and immunities observed in some countries [5], that are causing new epidemic waves, this commentary aims at generating further discussion and debate on the need to focus efforts in enhancing studies on long-term immunological response to and safety of COVID-19 vaccinations. Indeed, the existing body of evidence collected so far has been providing strong confirmation of short and mediumterm efficacy and safety of COVID-19 vaccines that confirmed vaccination as an essential tool for the control of the SARS-CoV-2 pandemic [1,[5][6][7][8][9]. However, questions as such as how long the protection obtained after vaccination lasts, as well as whether there are differences among age groups or sexes in vaccine effectiveness and safety, and best vaccination schedule for a life-long protection still need to be answered.…”
mentioning
confidence: 95%